Transposıtıon And Orthodontıc Treatment (A Report Of Two Cases) - Aslıhan Ertan Erdinç; Mustafa Ülgen (Galenos Yayinevi, 1995)
In this article, the literature survey of transposition and its etiology is briefly discussed. The orthodontic treatment of two cases with this rarely encountered abnormality is presented.